Motivation and task difficulty: A SOLO experience with adult learners - Tan, Hui Leng (penerbit ukm, 2006)
This study was conducted with a group of 26 PKPG teachers. A series of graded tasks for EDU 480 was set for these teachers, where task difficulty was controlled using the SOLO Taxonomy. These teachers were guided through the tasks. After six weeks on-task, a comparison of pre-task (Test 1) and post-task (Test 2) scores was done descriptively. There was a marked improvement in test scores. Feedback from these teachers and their instructor seems to indicate that this improvement may be related to their increased interest in the subject. They report that these adult learners are more motivated to study a subject where the learning process has enabled them to enjoy success in completing tasks especially tasks which were previously deemed difficult.